La producción y la comercialización de especies avícolas en las familias de la parroquia rural de Valparaíso, cantón Guano. - Tigse Guallan, Rocío Anabel (2023)
The present investigation has as a general objective to determine how the production affects the commercialization of poultry species in the families of the rural parish of Valparaíso of the Guano canton, for which it was necessary to carry out a diagnosis of the production and commercialization systems, identify the factors and propose a marketing model. For the methodology, it began by indicating that the Valparaíso parish is located in the province of Chimborazo, Guano canton, with an extension of 2144.3 ha, settling between 2810 and 4160 meters above sea level. In the investigation, the hypothetical-deductive method has been used, which starts from assertions as hypotheses and seeks to refute or falsify hypotheses to verify their veracity. The type of research was correlational with a non-experimental research design, carrying out the alternative hypothesis HI and the null hypothesis Ho, for which a survey was used that was applied to a sample of 140 people and said data was analyzed by means of IBM SPSS software. To verify the reliability of the instrument, the reliability analysis was carried out, obtaining a Cronbach's Alpha and then the hypothesis verification was carried out, the Chi Square test was applied, thus it was concluded that there are multiple factors that affect poultry production in the region, so constant monitoring of the practices of local producers is recommended to guarantee the effective implementation of the strategy.